Melanized fungal infections in kidney transplant recipients: contributions to optimize clinical management. (May 2017) - Santos, D.W.; Camargo, L.F.; Gonçalves, S.S.; Ogawa, M.M.; Tomimori, J.; Enokihara, M.M.; Medina-Pestana, J.O.; Colombo, A.L.
Abstract: Objectives: This is a retrospective and observational study addressing clinical and therapeutic aspects of melanized fungal infections in kidney transplant recipients. Methods: We retrospectively reviewed medical records of all patients admitted between January 1996 and December 2013 in a single institution who developed infections by melanized fungi. Results: We reported on 56 patients aged between 30 and 74 years with phaeohyphomycosis or chromoblastomycosis (0.54 cases per 100 kidney transplants). The median time to diagnosis post-transplant was 31.2 months. Thirty-four (60.8%) infections were reported in deceased donor recipients. Fifty-one cases of phaeohyphomycosis were restricted to subcutaneous tissues, followed by two cases with pneumonia and one with brain involvement. Most dermatological lesions were represented by cysts (23/51; 45.1%) or nodules (9/51; 17.9%). Exophiala spp. (34.2%) followed by Alternaria spp. (7.9%) were the most frequent pathogens. Graft loss and death occurred in two patients and one patient, respectively. Regarding episodes of subcutaneous phaeohyphomycosis, a complete surgical excision without antifungal therapy was possible in 21 of 51 (41.2%) patients. Long periods of itraconazole were required to treat the other 30 (58.8%) episodes of subcutaneous disease. All four cases of chromoblastomycosis were treated only with antifungal therapy. Conclusions: Melanized fungal infections should be considered in the differential diagnosis of all chronic skin lesions in transplant recipients. It is suggested that the impact of these infections on graft function and mortality is low. The reduction in immunosuppression should be limited to severely ill patients.